Rhinoplasty the experts' reference - Sclafani, Anthony P. (Thieme Medical Publishers Inc, 2015)
"Rhinoplasty: The Experts Reference is a comprehensive text that provides guidance from world-renowned experts on every aspect of rhinoplasty, from the functional to the cosmetic. The book opens with a section on initial patient assessment and consultation, moves on to such topics as surgery of the septum, with separate sections on the nuances of functional nasal surgery and revision rhinoplasty, and concludes with a section on avoiding and managing surgical complications. Each chapter is written by an expert on a specific topic and presents tried-and-true rhinoplasty techniques that can be readily implemented by facial plastic surgeons.Key Features: includes a section on ethnic rhinoplasty with chapters written by Drs. Tae-Bin Won, Russell W.H. Kridel, and Roxana Cobo; written by over 100 of the most well-known surgeons in the world, including Yong Ju Jang (Asia), Ira Papel, Stephen Park, Peter Adamson, and Rollin K. Daniel (North America), Wolfgang Gubisch, Charles East, Gilbert Nolst Trenite, and Pietro Palma (Europe), and Simon Robinson (Australia); Oofers expert solutions to a particular problem in each chapter. Practicing plastic surgeons and facial plastic surgeons, as well as residents and fellows in these fields, will consult this excellent desk reference whenever they are faced with a particularly challenging case"--Provided by publisher